Bio-insecticidal effects of Oleaster leaves aqueous extracts against Psylla larvae (Euphyllura olivina (Costa)), a primary pest of Olea europaea L. - Mestar, Nadjet G.; Boudiaf, Malika N.; Lahcene, Souad; Abbaci, Hocine; Aiche, Ghenima I.; Metna, Boussad; Saadoun, Noria S.; Taibi, Faiza; Houali, Karim (Cellular and Molecular Biology, 2018)
Many plant species produce phenolic compounds in their various organs and their use in crop protection. These plant secondary metabolites may serve as toxins against the insect pests. The objective of this study was to evaluate in vitro the bio-insecticidal effect of an aqueous extract of wild Olive leaves on Psylla larvae (Euphyllura olivina), a primary pest of the cultivated Olive tree (Olea europaea L. subsp sativa). Two concentrations of 0.05g/ml and 0.1g/ml leaves grinding powder in distilled water were sprayed on branches infested with Psylla larvae. The obtained results revealed a very significant mortality rate of the larvae 24 hours after spraying. The chemical composition of Oleaster leaves aqueous extracts is determined by HPLC-DAD. The results show in majority the presence of phenolic compounds represented by oleuropein and its metabolite hydroxytyrosol. The phenolic compounds of the crude extract were at the origin of this mortality. The Analysis of Variance revealed highly significant results both between the sampled trees and between the tested concentrations. The Principal Component Analysis (PCA) revealed a close relation between the physiological state of the studied trees and the degree of their infestation by the phytophagus. Taking into account, the physical and chemical characteristics of the sampled soils, data analysis showed that trees growing on nitrogen-rich soils were more infested than those growing on soils rich in organic carbon (Corg) and phosphorus (Porg).